2022
DOI: 10.3390/life12020266
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Hypertrophy Risk in Children Carriers of G-1082A Polymorphism of IL-10 Infected with Human Herpes Virus (HHV6, EBV, CMV)

Abstract: Adenoid hypertrophy (AH) is considered one of the most common diseases in the ear, nose and throat (ENT) practice. The cause of adenoid hypertrophy in children is still unknown. The main aim of the current study was to investigate IL-10 (interleukin 10) gene polymorphisms and human herpesviruses 6 (HHV6), cytomegalovirus (CMV), and Epstein–Barr virus (EBV) infections in children with AH. A total of 106 children with adenoid hypertrophy and 38 healthy children aged 2–11 years were included in this study. All ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…This susceptibility to infection may be caused by genetic dispositions. The role of different variations in inflammatory genetic factors, such as polymorphisms of mannose binding lectin (MBL), toll-like receptors (TLRs), secretoglobulins (SCGBs), or IL-10, were analyzed [ 20 , 21 , 22 , 23 ]. Grasso et al found that the MBL2 00 genotype is a prognostic marker of AH in children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This susceptibility to infection may be caused by genetic dispositions. The role of different variations in inflammatory genetic factors, such as polymorphisms of mannose binding lectin (MBL), toll-like receptors (TLRs), secretoglobulins (SCGBs), or IL-10, were analyzed [ 20 , 21 , 22 , 23 ]. Grasso et al found that the MBL2 00 genotype is a prognostic marker of AH in children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the work of Özdaş et al, the presence of single nucleotide polymorphisms (SNPs) of secretoglobulins were associated with an increased risk of AH [ 22 ]. Another study demonstrated the role of the IL-10 genotype GG in resistance to hypertrophy [ 23 ]. All these data support the hypothesis that the inheritance of AH is likely polygenic, involving aspects of physiology determined by multiple genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, патофизиология этого заболевания не до конца ясна. Выявление факторов, влияющих на иммунологический ответ, позволит получить важные данные для объяснения патогенеза ГГМ [54].…”
Section: заключениеunclassified
“…As part of Waldeyer’s ring of mucosa-associated lymphoid tissue (MALT), the adenoids play a role in upper-airway immunity as the first line of defense against inhaled or ingested pathogens [ 1 , 2 ]. Physiological growth of the adenoids peaks around the age of 7 years, and they tend to atrophy during adolescence [ 3 ]. Inflammation of the adenoids is called adenoiditis, which can cause a variety of symptoms.…”
Section: Introductionmentioning
confidence: 99%